Work and education in America : the art of integration - Barabasch, Antje [Herausgeber]; Rauner, Felix [Herausgeber] (Springer-Verlag, 2011)
This book brings together facts and figures on vocational education and training (VET) or career and technical instruction (CTE) in the United States. It "features insights into a variety of issues in this field of research. The international reader will find an up-to-date synthesis as well as a critical analysis of the relevant history, philosophy, governance, legislation and organizational structures. The coverage is structured according to the benchmarks applied to, as well as the theoretical discussions around, VET. The topics covered all have a strong contemporary relevance and include education versus qualification, the American community college, the issue of localization versus globalization in governance, vocationalism in higher education, career guidance and career counselling, and apprenticeships in the U.S." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; S 4.3 Steuerung; G 1.2.3 Qualifikationsentwicklungen; L 6.2 Qualitätsmanagement/Qualitätssicherung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.3.2 Nordamerika; Berufsbildungssystem; Berufsausbildung; Hochschulbildung; Bildungssteuerung; Qualifikationsentwicklung; Berufswegplanung; Qualitätssicherung; Lehrerbildung; Durchlässigkeit im Bildungssystem; Zukunftsperspektive; USA